RETRACTED: Globally, Freshwater Ecosystems Emit More CO2 Than the Burning of Fossil Fuels - Pollard, Peter C. (Frontiers in Environmental Science, 2022)
Freshwater emits substantial volumes of CO2 to the atmosphere. This has largely gone unnoticed in global carbon budgets. My aim was to quantify the CO2 emanating from freshwater from 66° N to 47° S latitudes via in situ bacterial respiration (BR). I determined BR (n = 326) as a function of water temperature. Freshwater is emitting CO2 at a rate of 58.5 Pg C y−1 (six times that of fossil fuel burning). Most is emitted from the Northern Hemisphere. This is because the high northern summer temperatures coincide with most of the world’s freshwater. Diffuse DOC sources, for example dust, may be driving high freshwater BR. However, many sources remain elusive and not individually quantified in the literature. We must include freshwater CO2 emissions in climate models. Identifying, quantifying and managing freshwater’s diffuse sources of Dissolved Organic Carbon (DOC) will hopefully provide us with another opportunity to change our current climate trajectory.